THE IMPORTANCE OF PLAY WHILE LEARNING TO HONE INTELLIGENCE MOTORCYCLES IN THE MIDDLE OF THE COVID-19 PANDEMIC AT TABRIYATUL AITAM ORPHANAGE, MOJOSARI MOJOKERTO - Dwi Dewianawati (Bajang Institute, 2021)
The targets and objectives of this activity are the foster children of the Tarbiatul Aitam orphanage who need basic leadership training to shape the character and personality of the child. So it is hoped that by participating in these activities, they can hone their motor intelligence by playing while learning. The foster children of the Tarbiatul Aitam orphanage are very compact, especially in terms of togetherness. Foster children of the Tarbiatul Aitam orphanage put more emphasis on the religious side such as memorizing the holy verses of the Koran, prayer, banzaria, routine readings, annual circumcision etc. This proves that Tarbiatul Aitam orphanage children have a lot of potential to support activities in the orphanage. The problem faced is that there are still many children who feel insecure, at least they have an achievement and many are still ashamed of the slow pace and spontaneity of their activities. The method used is lectures, and direct practice with games where each has its own purpose and meaning. The program carried out is fostering children through learning while playing activities, the participants are orphans with a total of 22 men and women. Participants or orphans would like to thank the academic community of Unimas Mojokerto for providing useful knowledge to orphans in order to foster leadership motivation, courage and confidence in socializing in the orphanage and community. And hope there will be ongoing activities with different themes.